SPE Annual Technical Conference and Exhibition 2011
DOI: 10.2118/146697-ms
|View full text |Cite
|
Sign up to set email alerts
|

Practical and Operational Use of Assisted History Matching and Model-Based Optimisation in the Salym Field

Abstract: History matching and future production optimisation in reservoir modelling is being done more and more with the help of automated or assisted computing techniques, such as design of experiments, Ensemble Kalman Filtering or adjoint- and other gradient-based techniques. With the advent of these techniques, reservoir engineers also get less trivial applications of computer assisted optimisation at their disposal. In this paper we will present two such non-trivial applications. In the first example… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…It is also well known that the estimated parameter values in such unregularized illposed problems are extremely sensitive to noise in the data. Joosten et al (2011) introduced the model maturation concept and showed that sometimes the application of unregularized reservoir parameter estimation still appears to have added value. They showed that localized unrealistic parameter values can be used as an indicator of model errors (or under-modeling) in the underlying reservoir model.…”
Section: Bayesian Parameter Estimationmentioning
confidence: 99%
“…It is also well known that the estimated parameter values in such unregularized illposed problems are extremely sensitive to noise in the data. Joosten et al (2011) introduced the model maturation concept and showed that sometimes the application of unregularized reservoir parameter estimation still appears to have added value. They showed that localized unrealistic parameter values can be used as an indicator of model errors (or under-modeling) in the underlying reservoir model.…”
Section: Bayesian Parameter Estimationmentioning
confidence: 99%
“…As part of our Best Practices we employ a workflow consisting of Experimental Design and the Adjoint Method with an emphasis on understanding rather than on automatically obtaining history matched models (Joosten & Altintas (2011), Van Doren et.al. (2012, van Essen et.al.…”
Section: Assisted History Matchingmentioning
confidence: 99%
“…This is illustrated in Figure 3b from Joosten & Altintas (2011). However, best practice has shown that the resulting model parameters should never be used blindly without relating the updates to physical explanations.…”
Section: Assisted History Matchingmentioning
confidence: 99%
See 1 more Smart Citation
“…The motivation stems from a paper by Joosten et al (2011) who showed that sometimes the application of unregularized reservoir parameter estimation still appears to have added value. They argued, based on numerical examples, that localized unrealistic parameter values can be used as an indicator of model errors in the underlying reservoir model.…”
Section: Introductionmentioning
confidence: 99%